Makna Dakwah Kultural dalam Tradisi Tedhak Siten Desa Mlilir, Kecamatan Dolopo, Kabupaten Madiun - Regiana Yaumil Rahma Rahma; Muhammad Irfan Riyadi Riyadi (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2025)
The Tedhak Siten tradition, as part of Javanese culture, is a traditional procession of going down to the ground that is carried out by a baby when he begins to learn to set foot on earth. This tradition is not only understood as a cultural heritage, but also as a medium for conveying religious values in the context of cultural preaching. This study aims to examine how the process of tradition, the meaning of preaching in the procession, and the meaning of preaching in the symbols of artifacts in the Tedhak Siten tradition in Mlilir village. This study uses a qualitative method with a qualitative descriptive research type. Data were obtained through interviews with community leaders, religious leaders, and tradition practitioners, and researchers also observed directly the implementation of the ritual and documented the event ritual. The results of the study show that the Tedhak Siten tradition contains elements of preaching in the process, meaning, and cultural symbols. Ritual processions such as thanksgiving, and the hope of parents' prayers for their children contain moral and spiritual messages that reflect Islamic teachings about piety, gratitude, and character building. This finding confirms that the meaning of the Tedhak Siten tradition and the symbols of the tradition not only function as a cultural heritage, but also as a medium of preaching that strengthens Islamic values in the lives of the community.